1998
DOI: 10.1007/s004649900763
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of endometrial trocar site implantation

Abstract: We present the case of a 35-year-old woman with a history of apparent bilateral hernia who had a surgical intervention that included a diagnostic laparoscopy converted to open laparotomy. The patient experienced endometrial implants exclusively at trocar sites. This case is cited as validation of the pneumoperitoneum-induced free cell implantation theory, or the so-called aerosolization theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…It can be observed after Cesarean section [2,3] and after episiotomy at the perineal site [4]. Surgical scar endometriosis at the trocar site has been described to be associated with the use of laparoscopic surgery as a method for treatment [5,6]. In our case, a symptomatic lesion was observed to develop three years after her laparoscopic hysterectomy, yet there was no endometriosis lesion noted at that time.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…It can be observed after Cesarean section [2,3] and after episiotomy at the perineal site [4]. Surgical scar endometriosis at the trocar site has been described to be associated with the use of laparoscopic surgery as a method for treatment [5,6]. In our case, a symptomatic lesion was observed to develop three years after her laparoscopic hysterectomy, yet there was no endometriosis lesion noted at that time.…”
Section: Discussionmentioning
confidence: 66%
“…The infl uence of surgical tumor manipulation and the resultant shedding of tumor cells has been observed [7]. It has also been suggested that localized tissue ischemia renders that tissue conductive to implantation [6]. Several authors have hypothesized that the practice of insuffl ating CO 2 into the peritoneal cavity causes cell aerosolization and may promote tumor cell shedding [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In searches of the PubMed, Google Scholar, and Medline databases using the search terms ''endometriosis,'' ''scar endometriosis,'' ''abdominal wall endometriosis,'' and ''trocar,'' alone and in various combinations, we found 14 English-language articles on trocar site endometriosis. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Table 1 summarizes the data from the 10 articles (13 patients) for which we obtained the full text.…”
Section: Case Reportmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18] This study presents the case of a patient with endometriotic trocar site metastasis who had previously undergone laparoscopic resection of a left ovarian endometriotic cyst.…”
mentioning
confidence: 99%